The accuracy of food and drink cards as a tool for estimating total nutrients and calories intake - Ardesy Melizah Kurniati; Arisman Arisman; Minerva Riani Kadir (JURNAL KEDOKTERAN DAN KESEHATAN, 2019)
Interview method in exploring foods and drinks intake require estimation tool. Household measuring instruments can be used, as well as of food photographs and three-dimension food models. The purpose of this study was to assess the accuracy of food and drink cards as a tool to estimate the portion of real food and drink. A total of 32 respondents participated in this study. Food records were collected then body weight and height of respondents were measured. In the following day, the respondents estimated the portion of the real foods and drinks compare to the cards. Fifty-one cards are considered accurate from the total 67 cards. Food and drink cards can be used as a tool to estimate nutritional intake and total calories.